Profil Anafilaksis di RSU Hasanah Graha Afiah, Depok pada Januari 2023 – April 2024 - Koesnoe, Sukamto; Wulandari, Risky; Wicaksana, Bramantya (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Anaphylaxis is a severe hypersensitivity reaction that occurs rapidly and can be life-threatening. This reaction disrupts the respiratory, cardiovascular, digestive, and/or integumentary systems. The global prevalence of anaphylaxis is 1-2%, with a mortality rate of 0.3%. However, data on anaphylaxis in Indonesia is very limited. The aim of this study was to obtain anaphylaxis profile at Hasanah Graha Afiah Hospital, Depok. Methods. This study used a cross-sectional descriptive study from January 2023 to April 2024 at Hasanah Graha Afiah Hospital, Depok, Jawa Barat. Inclusion criteria include patients aged ≥17 years, diagnosed with anaphylaxis in medical records in inpatient and/or emergency units. Data was collected from electronic medical records. Demographic variables include gender, age, marital status, occupation, education, comorbidities, causes of anaphylaxis, diagnostic criteria, severity, initial therapy, and mortality. Results.This study found an anaphylaxis incidence rate of 0.8%, with the highest occurrence in the 26-35 age group (28%). Most anaphylaxis cases were in females (59%). The most common triggers were NSAIDs (34.4%), followed by antibiotics (28.1%), paracetamol (9.4%), anti-bleeding agents (9.4%), and anti-tuberculosis drugs (6.2%). Interestingly, we found food, blood products, and cold as other causes. Anaphylactic shock occurred in 19% of cases. The most used therapies were methylprednisolone (43%), diphenhydramine (28%), epinephrine (17%), and dexamethasone (12%). There were no anaphylaxis-related mortalities. Conclusions. The incidence of anaphylaxis at RSU Hasanah Graha Afiah, Depok, was 0.8%. Most cases occurred in females aged 26–35 years, with medications being the primary trigger. Vigilance in selecting disease treatment, early recognition of anaphylaxis, and prompt and appropriate management are essential instruments in the successful handling of anaphylaxis.